Simulation of hydrogen adsorption on modified carbon structures - Chandra Wahyu Purnomo (Jurnal Rekayasa Proses, 2007)
The adsorption simulation of hydrogen molecules onto modified carbon structures has been carried out. The modifications have been done by rearranging carbon nanotube structure and also by replacing carbon molecules by impurities i.e. boron and nitrogen atoms. The aims of this simulation isfinding an optimum adsorption delivery of each modified carbon structures leading to an effective gas storage system. The adsorption simulation has been carried by Grand Canonical Monte Carlo methods (GCMC). By this simulation, it wasfound that the optimum temperaturefor hydrogen adsorptiondelivery was still under room temperature.